2003
DOI: 10.1099/mic.0.26119-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of dipeptidyl peptidase IV from the ruminal bacterium Prevotella albensis M384T

Abstract: Ruminal bacteria of the genus Prevotella play a crucial role in peptide breakdown in the rumen, a component of protein catabolism that leads to the inefficient use of dietary protein by ruminant animals. This is the first report of the cloning of a peptidase gene from a ruminal bacterium. Part of the dipeptidyl peptidase type IV (DPP-IV) gene from Prevotella albensis M384 T was cloned using degenerate primers designed from conserved regions found within other known DPP-IV sequences. Flanking regions were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…The substrate showing the highest affinity for the recombinant DPP IV was Gly-Pro-pNa, with a K m of 0.26 mM and a V max of 7.8 mol mg Ϫ1 min Ϫ1 . This value is comparable to those reported for P. albensis (27) and L. helveticus (26). The recombinant DPP IV also had significant affinity for Lys-AlapNa (K m of 0.87 mM) and Ala-Pro-pNa (K m of 12 mM) with V max values of 5.9 and 30 mol mg Ϫ1 min Ϫ1 , respectively.…”
Section: S Suissupporting
confidence: 84%
See 3 more Smart Citations
“…The substrate showing the highest affinity for the recombinant DPP IV was Gly-Pro-pNa, with a K m of 0.26 mM and a V max of 7.8 mol mg Ϫ1 min Ϫ1 . This value is comparable to those reported for P. albensis (27) and L. helveticus (26). The recombinant DPP IV also had significant affinity for Lys-AlapNa (K m of 0.87 mM) and Ala-Pro-pNa (K m of 12 mM) with V max values of 5.9 and 30 mol mg Ϫ1 min Ϫ1 , respectively.…”
Section: S Suissupporting
confidence: 84%
“…The deduced amino acid sequence from the nucleotide sequence revealed that it contained a complete open reading frame coding for a 755-aminoacid protein with a calculated molecular mass of 85 kDa. This correlates well with the molecular masses previously reported for other DPP IVs, including those from P. albensis (27), S. gordonii (7), Lactobacillus sakei (20), and S. thermophilus (25).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In the rumen they are symbionts contributing to the degradation of plant cell-wall polysaccharides (Miyazaki et al, 2003) and protein metabolism (Walker et al, 2003), whereas oral prevotellas are implicated in dental plaque establishment (Kolenbrander et al, 2002), periodontitis (Paster et al, 2001), advanced caries (Martin et al, 2002), oro-pharyngeal abscesses (Brook, 2004) and noma, a grotesque childhood orofacial gangrene, now confined mostly to sub-Saharan Africa (Enwonwu et al, 2006). The genetic tools that would make possible more thorough studies of prevotellas are still undeveloped despite their ecological and medical importance.…”
Section: Introductionmentioning
confidence: 99%